Experimental study of aerodynamic force coefficients for a bridge deck sitting above water waves. Issue 226 (July 2022) - Yin, Rui-Tao; Zhu, Bing; Yang, Zhen-Yu; Yang, Zhi-Ying; Guo, Chen; Cui, Shengai
Abstract: This study presents an experimental investigation of the aerodynamic force coefficients for a bridge deck sitting above water waves based on wind tunnel and wave flume tests. A deck sectional model with a scale ratio of 1:60 was manufactured and tests were performed in a wind tunnel and wave flume. A test system that conducts the aerodynamic tests was built, and the aerodynamic forces of the deck sectional model in the wind-only field and wind-wave coupled field were then measured. The studied parameters include four regular wave heights ( H ), four bridge clearances ( a ), three wind speeds ( U ), three regular wave periods ( T ), and nine angles of attack in the range −12° ≤  α  ≤ +12°. The test results indicated that the time histories of the aerodynamic force coefficients of the deck sectional model change periodically in the wind-wave coupled field, and the variation periods are approximately consistent with the regular wave period. The smaller the relative bridge clearance ( a / H ), the more significant the effect of the regular wave on the aerodynamic forces of the deck sectional model. The differences among the maximum aerodynamic force coefficients of the deck sectional model in the wind-wave cases for different relative bridge clearances ( a / H ) are significantly larger than those for different relative propagation velocities ( U / c ) and different parameter groups ( T  ∼ ( λ, c )), so are the differences among the minimum aerodynamic force coefficients. Highlights: A stand device system which is suitable for the wind tunnel and wave flume was designed and manufactured, based on which the test system that can conduct the aerodynamic tests of a deck sectional model was built. A laboratory technique for a bridge deck in the wind-wave coupled field was explored and the aerodynamic force coefficients of the deck sectional model were studied. The aerodynamic forces of the bridge deck in the wind-only field and wind-wave coupled field were measured, and the variation laws of the aerodynamic force coefficients under the effects of the studied parameters were analyzed.